STUDENTS‘ PERCEPTION ON THE USE OF REFLECTIVE LEARNING PORTFOLIO IN TEACHING WRITING - Ida Yulianawati; Januarius Mujiyanto; Mursid Saleh; Djoko Sutopo (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
This study aimed at investigating students’ perception on the use of Reflective Learning Portfolio (RLP) in teaching writing. This study, which followed the case study design, was conducted in a class of 31 students at a university in Indramayu, Indonesia. During one semester, the reflective learning portfolio (RLP) was used as the treatment to teach writing. Questionnaire and interview were given to students to express their perception to the use of reflective learning portfolio in their classroom. The result of the study  shows that most students believed reflective learning portfolio give positive impact on their writing. The reflective learning portfolio involves learners in a process of continues reflection on their work and collaboration with their peers and lecturer which has focus on selective evidence of learning that makes students become involved in self-evaluation and begin to monitor their own progress over time.